Impact of KVK training on knowledge and adoption levels of soybean growers in Maharashtra State: IMPACT OF KVK TRAINING ON KNOWLEDGE AND ADOPTION LEVELS OF SOYBEAN GROWERS - S K DESHMUKH; G TAMILSELVI (Journal of Oilseeds Research, 2021)
The study was conducted in ten selected villages of Washim District of Maharashtra to study the impact of training programs conducted by KVK, Karda on knowledge and adoption levels of soybean growers. The sample comprised of 150 trainees and 150 non-trainees from the KVK operated villages. The results of the study revealed that the trainee farmers had higher knowledge and adoption levels on improved soybean cultivation practices than the non-trainee farmers. The scores of knowledge and adoption indices for varioussoybean cultivation practices were also found to be more for trainee farmers than their counterparts. This indicated that KVK played a significant role in increasing the knowledge and adoption levels of soybean growers.